PENGARUH GAYA KEPEMIMPINAN SITUASIONAL DAN KOMUNIKASI ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. SWADHARMA SARANA INFORMATIKA PEKANBARU - Andharsih, Dhea; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted at PT Swadharma Sarana Informatika Pekanbaru with a problem in the study is the low performance of employees. The purpose of this study is to determine and analyze the influence of situasional leadership style and organizational communication on employee performance partially and simultaneously. This study uses a questionnaire as a data collection tool that is distributed to 67 respondents to employees of PT Swadharma Sarana Informatika Pekanbaru. The data is then processed using descriptive analysis and quantitative analysis using SPSS by conducting validity, reliability testing, simple linear regression analysis, multiple linear regression analysis, determination analysis (R2) and hypothesis testing by t (partial) and F (simultaneous) testing.The results showed that the first hypothesis testing which is situasional leadership style on employee performance was tcount (6,051) > ttable (1.997), meaning that situasional leadership style significantly influenced employee performance. Second organizational communication of employee performance is tcount (5,384)> ttable (1.997), meaning that organizational communication al has a significant effect on employee performance. The results of Fcount (24,911)> Ftable (3,14) means that situasional leadership style and organizational communication have a significant effect on employee performance. Â Keywords: situasional leadership style, organizational communication, Employee Performance